(Invited) Control of Internal Plasma Parameters Toward Atomic Level Processing. (16th August 2016) - Sekine, Makoto; Tsutsumi, T; Fukunaga, Y; Takeda, K; Kondo, H; Ishikawa, K; Hori, M
Abstract : Plasma processes have been indispensable core technologies to manufacture ultra-large scale integrated circuits and variety of devices. To develop the next generation devices, advancing of the plasma processes should be needed. Towards the surface processing with atomic level accuracy with low damage, the precise control of internal parameters that actually define the surface reaction has become more important. We have developed an autonomous plasma manufacturing system, which measures the densities of some atomic species with a compact monitoring system and controls them at optimum values in real time. The spatiotemporal fluctuation of species in the plasma affects much on the surface reactions, which is fatal to fabricate nano-size, atomic level structures. Then, we can make nano-scale etching with an ultrahigh precision by employing the autonomous plasma system.